A Twisted Thieno[3, 4‐b]thiophene‐Based Electron Acceptor Featuring a 14‐π‐Electron Indenoindene Core for High‐Performance Organic Photovoltaics. Issue 43 (6th October 2017) - Xu, Sheng jie; Zhou, Zichun; Liu, Wuyue; Zhang, Zhongbo; Liu, Feng; Yan, Hongping; Zhu, Xiaozhang
Abstract: With an indenoindene core, a new thieno[3, 4‐ b ]thiophene‐based small‐molecule electron acceptor, 2, 2′‐((2Z, 2′Z)‐((6, 6′‐(5, 5, 10, 10‐tetrakis(2‐ethylhexyl)‐5, 10‐dihydroindeno[2, 1‐a]indene‐2, 7‐diyl)bis(2‐octylthieno[3, 4‐b]thiophene‐6, 4‐diyl))bis(methanylylidene))bis(5, 6‐difluoro‐3‐oxo‐2, 3‐dihydro‐1H‐indene‐2, 1‐diylidene))dimalononitrile (NITI ), is successfully designed and synthesized. Compared with 12‐π‐electron fluorene, a carbon‐bridged biphenylene with an axial symmetry, indenoindene, a carbon‐bridged E ‐stilbene with a centrosymmetry, shows elongated π‐conjugation with 14 π‐electrons and one more sp 3 carbon bridge, which may increase the tunability of electronic structure and film morphology. Despite its twisted molecular framework, NITI shows a low optical bandgap of 1.49 eV in thin film and a high molar extinction coefficient of 1.90 × 10 5 m −1 cm −1 in solution. By matchingNITI with a large‐bandgap polymer donor, an extraordinary power conversion efficiency of 12.74% is achieved, which is among the best performance so far reported for fullerene‐free organic photovoltaics and is inspiring for the design of new electron acceptors. Abstract : A thieno[3, 4‐ b ]thiophene‐based electron acceptor, NITI, featuring a 14‐π‐electron indenoindene core is designed and synthesized. Despite its twisted molecular geometry, NITI shows a low optical bandgap and a high molar extinction coefficient. By matchingNITI with a large‐bandgap polymer donor, an extraordinary power conversion efficiency of 12.74% is achieved, which represents an exciting progress in the design of new electron acceptors.